Preparing for tomorrows health challenges: lessons from a COVID-19 epidemic from tertiary healthcare setting in Delhi - Walecha, Ambika; Goel, Manish Kumar (International Journal of Research in Medical Sciences, 2024)
Background: The COVID-19 pandemic highlighted the fragility of healthcare systems, underscoring the urgent need for preparedness in managing medical emergencies. This study aims to evaluate the strengths and challenges within a tertiary care hospital, focusing on the lessons learned to improve future crisis management. This qualitative study investigates the strengths and limitations of Lady Hardinge medical college and associated hospitals during the COVID-19 pandemic. The findings aim to contribute to the development of a standardized preparedness plan for future epidemics and medical emergencies. Methods: Ethical approval was obtained, and confidentiality was maintained. The research was conducted from August 2022 to December 2023 using purposive sampling. Data were collected through interviews and focus groups with hospital staff across all levels, including administrators, faculty, residents, nurses, paramedics, and support staff. Thematic analysis was used to identify key patterns and themes related to hospital preparedness and response strategies. Results: Key themes emerged around service delivery challenges, communication issues between departments, resource management, and psychological concerns such as the need for acknowledgment. Insights from staff during the first and second waves of the pandemic revealed both weaknesses and strengths, providing valuable lessons for managing future emergencies. Conclusions: The study emphasizes the importance of addressing the identified challenges to strengthen hospital systems for future crises. The findings offer essential guidance in developing effective preparedness plans to enhance healthcare resilience during emergencies.